Um teto todo nosso: Leia Mulheres Cascavel e suas reverberações - Sergel, Caroline (2023)
The research presented here is the result, first and foremost, of my personal experience as a participant in the Leia Mulheres Cascavel reading club, which became the object and theme of this study when it prompted me to question what the reverberations of the reading club would be on other participants. In order to address such issue and with the objective of situating the socio-historical location of the participants and the authoresses read, I support the research with a participative approach methodology. The data collection was made possible through interviews with the reading club mediators and a questionnaire applied to the participants. As a result of this investigative process, it was possible to observe what Leia Mulheres Cascavel meant and means to those who are part of it, the other activities carried out by it, and how it was and has been constructed as a space for disseminating culture in the city, encouraging the reading of works written by women, and discussing themes that transcend the social fabric.